PERAN PEMERINTAH DESA DALAM MENGELOLA WISATA HUTAN PINUS UNTUK MENINGKATKAN PENDAPATAN ASLI DESA DI DESA BENDOSARI, KECAMATAN PUJON, KABUPATEN MALANG - Dewi Citra Larasati; Ya’taufiq Kurrahman (Universitas Tribhuwana Tunggadewi, 2019)
This study aimed to determine the role of the village government in managing pine forest tourism to increase the Village Original Revenue (PAD) in Bendosari Village, Pujon District, Malang Regency and identify the problems faced by the Bendosari Village Government. The study used a qualitative method with data collection technique using a combination of interviews, observation, and documentation triangulation. While the sampling technique used Puporsive Sampling. From this research, the results showed that the role of Bendosari village government were disseminating and planning the development of pine forest tourism areas, forming POKDARWIS, conducting tourism promotion on social media, and conducting comparative studies in other tourist villages. While the factors that influenced the implementation were the natural conditions that were affected during the rainy season and the human resources, such as the lack of awareness and ability of the community to manage the pine forest tourism. So there is a need for an intensive training and mentoring from the Bendosari village government.